Class: A Guide Through the American Status System (an excerpt) - Paul Jr. Fussell (Journal of Economic Sociology, 1970)
This book presents a comprehensive and carefully researched guide to the American class system. Professor Fussell distinguishes between classes using not a criterion of inborn features or hidden observation preferences, but by using visible demonstrations of choice. Fussell describes the lifestyles of people in each class, from the way they dress and where they live to their education and hobbies. Journal of Economic Sociology publishes the first chapter, “A Touchy Subject,” in which Fussell indicates that in the United States, class differences are complex and subtle and that the existence of a class structure in the country is questioned. However, Fussell considers that a refusal to answer the question about social classes as well as a hostile response to the question indicate that in a given society there is a class system.